Reflections on Dry Eye Syndrome Treatment: Therapeutic Role of Blood Products - Drew, Victor J.; Tseng, Ching-Li; Seghatchian, Jerard; Burnouf, Thierry (Frontiers in Medicine, 2018)
Dry eye syndrome (DES) is a multifactorial, frequent, pathology characterized by deficient tear production or increased evaporation of tears, and associated with ocular surface alteration and inflammation. It mostly affects, but not exclusively, older individuals and leads to varying degrees of discomfort and decreased quality of life. While the typical treatments of DES rely on using artificial tears, polyunsaturated fatty acids, integrin antagonists, anti-inflammatory agents, or on performing punctual occlusion, recently, standardized non components blood-derived serum eye drops (SED) are generating much interest as a new physiological treatment option. The scientific rationale in using SED for treating or releasing the symptoms of DES is thought to lie in its composition in multiple factors that resembles that of tears and contributes to the healing and protection of the ocular surface. This manuscript seeks to provide relevant background information on the management of DES, and on the increasing role that various types of SED or platelet lysates, from autologous or allogeneic origins, are playing in the improved therapeutic management of this pathology. The increasing role played by blood establishments in producing better-standardized SED is also addressed.